Nilai-Nilai Islam Dalam Bahan Ajar Tematik Makananku Sehat Dan Bergizi: Suatu Konsep Integratif Pembelajaran Di Madrasah Ibtidaiyah - Munir, Misbahul (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2015)
Internalization of religious values in accordance with the circumstances and conditions that are educational environment. In environmental and historical roots, madrasah system can not be separated from the symbol ofIslam as a public education forum distinctively Islamic religious. Incorporating Islamic values in teaching materials tematic in madrassas have a very important role in giving directions the life of mankind. Islamic values derived from religious instructions as a guide in efforts to achieve a meaningful life in the context of teaching materials thematic my food healthy and nutritious value of Islam can be tangible in the sub-theme (1) Halal Food and Thayyib, (2) Avail Halal Food and Thayyib, (3) Adab Eat Messenger.Keywords: Islamic values, thematic materials